PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA KOPERASI KREDIT OBOR MAS CABANG UTAMA ENDE - Tanusi, Gabriel (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2022)
Good working capital management can increase the value of cooperative profitability which is indicated by the residual value of operating results (SHU). This study aims to determine and analizy the management of working capital at Kopdit Obor Mas Cabang Utama Ende years 2018 - 2020 in increasing. The type of used is quantitative data sourced from secondary data in the form of financial balance report and calculations of remaining operating results for 2018 - 2020. The data analysis technique uses the analysis of working capital turnover ratio and profitability ratio The results of the study show that working capital turnover fluctuates where for 2019 it has increased but in 2020 it has decreased so that it affects the acquisition of fluctuating profitability value s indicated by the ratio NPM, ROA, ROE. Efforts to increase profitabiity can br done by using cash optimaly so that there is no idle cash, increasing receiveble collection so as not to cause a buildup of working capital on receivables and controlling operational and non operational cost